Correlation Between Demographic Factors (Age, Gender, and Living Area) and Tuberculosis Notification Rates in Private Healthcare: a Cross-sectional Study - Suryanti, Suryanti; Ahmed, Idris Adewale; Hamzah (International Journal of Health Literacy and Science, 2025)
Tuberculosis (TB) remains a critical global health challenge, causing approximately 1.3 million deaths in 2022. Indonesia, ranking second globally in TB burden, faces substantial issues with under-reported TB cases, with nearly 30% unnotified due to barriers such as limited healthcare access, inadequate diagnostics, and inconsistent reporting systems. This study investigates the relationship between patient demographic factors — age, gender, and living area—and the under-reporting of TB cases in Indonesia’s private healthcare sector. Using Spearman correlation analysis, the study identified a significant association between living area and TB under-reporting (p < 0.05), highlighting disparities between urban and rural regions. In contrast, no significant correlations were observed for age or gender (p > 0.05). The findings emphasize the urgent need for strengthening healthcare infrastructure and implementing standardized digital reporting systems to address regional disparities and improve case notification rates. These insights provide critical guidance for policymakers and healthcare professionals in designing targeted interventions to reduce TB under-reporting and enhance public health outcomes.